THE EFFECTIVENESS OF DCD AND FORWARD CONTRACT IN MANAGING FOREIGN EXCHANGE RISK - Apriani Dokas Rambu Atahau; Surya Wibowo (Journal of Management and Business, 2008)
Globalization has increase the nature of competition among firms, mainly firms engaged in international trading by the increasing volatility of exchange rates. The existence of the unavoidable foreign exchange risk has brought the development of various kinds of foreign exchange risk management tools; include hybrid securities such as Dual Currency Deposit (DCD) introduced by Development Bank of Singapore. This paper tries to elaborate the effectiveness of DCD innovative instruments in minimizing foreign exchange risks compare to traditional forward contract. The analysis tool being used is option theory applied to data of an innovative product. The results showed that prediction of future spot rate plays a vital role in deciding instruments choose to manage foreign exchange risk. Hence, it is desirable to predict the direction and magnitude of future spot rate in order to optimize the effectiveness of both instruments.